The Basics of Biosolids Application to Land in Florida - Thomas A. Obreza; George A. O'Connor (EDIS)
Biosolids are nutrient-rich, predominantly organic materials. Although classified as a waste material, biosolids can be a beneficial agricultural or horticultural resource because they contain many essential plant nutrients and organic matter. Following proper treatment and processing, biosolids can be recycled as fertilizers or soil amendments to improve and maintain productive soils and stimulate plant growth, with negligible human health or environmental impacts. This document is SL 205, a fact sheet of the Soil and Water Science Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First printed: April 2003.